2021
DOI: 10.1016/j.jsxm.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Pneumonia Affects Male Reproductive Hormone Levels: A Prospective, Cohort Study

Abstract: Background: SARS-CoV-2 which causes coronavirus disease 2019 binds to angiotensinconverting enyzme 2 (ACE2) and enters the host cell. ACE2 protein is expressed highly in the testis. Aim: The aim of this study was to compare male reproductive hormones such as total testosterone (TT), luteinizing hormone (LH), follicular stimulant hormone (FSH), and prolactin between patients with COVID-19, age-matched cases with noneCOVID-19 respiratory tract infection, and age-matched controls. Methods: This was a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
96
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 38 publications
13
96
0
2
Order By: Relevance
“…Çayan et al 30 showed that COVID‐19 could decrease circulating T levels, and lower T levels at baseline were associated with a significantly increased risk in terms of ICU and mortality. Similarly, Kadihasanoglu et al recently reported the findings of a prospective cohort study where male patients with COVID‐19 have been compared with men with non‐COVID‐19 respiratory tract infection and age‐matched controls; interestingly enough, testosterone deficiency was found in almost 74% of men with COVID‐19, and serum tT levels were significantly correlated with a longer hospitalization time 31 …”
Section: Discussionmentioning
confidence: 89%
“…Çayan et al 30 showed that COVID‐19 could decrease circulating T levels, and lower T levels at baseline were associated with a significantly increased risk in terms of ICU and mortality. Similarly, Kadihasanoglu et al recently reported the findings of a prospective cohort study where male patients with COVID‐19 have been compared with men with non‐COVID‐19 respiratory tract infection and age‐matched controls; interestingly enough, testosterone deficiency was found in almost 74% of men with COVID‐19, and serum tT levels were significantly correlated with a longer hospitalization time 31 …”
Section: Discussionmentioning
confidence: 89%
“…42 The testicular injury reported in these studies could also be a consequence of alterations in the coagulative status, resulting in development of ischemia at a microvascular level. 43 Independently of the etiology, testicular damage can possibly lead to the development of a form of hypergonadotropic hypogonadism [44][45][46][47][48] : As testosterone modulates endothelial function, 49 the possible effects of COVID-19 on erection could also be indirectly due to impaired testosterone secretion from the affected testis, besides the known direct effects of testosterone in male sexual response. 50 Additionally, as higher testosterone levels are also associated with lower levels of pro-inflammatory cytokines such as tumor necrosis factor alpha (TNFα), interleukins (IL-6 and IL-1β), and higher levels of anti-inflammatory cytokines (such as IL-10), 51 the "immunothrombotic" mechanism described for COVID-19 52 and involving the same cytokines 5,53 could be promoted by the hypogonadal state encountered in affected patients.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 99%
“…Lower testosterone and higher LH levels in comparison of active COVID-19 patients with age-matched healthy controls were reported [8,17,18]. Similarly, male patients with COVID-19 had lower testosterone levels even in comparison with non-COVID-19 respiratory tract infections and age-matched controls [19]. This may point to a specific pathogenic impact on testicular functions rather than acute phase hypogonadism [20].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, testosterone could predict the outcomes of hospitalized COVID-19 patients. Hypotestosteronemia was linked with increased risk in terms of ICU and mortality [19], need of mechanical ventilation or mortality [17], and higher risk of ICU admission and death outcomes [21]. Moreover, testosterone levels were significantly associated with a longer time of hospitalization [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation